Unified Protocol for the transdiagnostic treatment of emotional disorders in people with post COVID-19 condition: study protocol for a multiple baseline n-of-1 trial - Martínez-Borba, Verónica; Martínez-García, Laura; Peris-Baquero, Óscar; Osma, Jorge; del Corral-Beamonte, Esther (Frontiers in Psychology, 2023)
Background: Post COVID-19 syndrome, defined as the persistence of COVID-19 symptoms beyond three months, is associated with a high emotional burden. Post COVID-19 patients frequently present comorbid anxiety, depressive and related disorders (emotional disorders, EDs) which have an important impact on their quality of life. Unfortunately, psychological interventions to manage these EDs are rarely provided to post COVID-19 patients. Also importantly, most psychological interventions do not address comorbidity, namely simultaneous EDs present in COVID-19 patients. This study will explore the clinical utility and acceptability of a protocol-based cognitive-behavioral therapy called the Unified Protocol for the transdiagnostic treatment of EDs in patients suffering post COVID-19 condition. Methods: a multiple baseline n-of-1 trial will be used, as it allows participants to be their own comparison control. Sample will be composed of 60 patients diagnosed with post COVID-19 conditions and comorbid EDs from three Spanish hospitals. After meeting the eligibility criteria, participants will answer the pre-assessment protocol and then they will be randomly assigned to three different baseline conditions (6, 8 or 10 days of assessments before the intervention). Participants and professionals will be unblinded to participants' allocation. Once the baseline assessment has been completed, participants will receive the online psychological individual intervention through video-calls. The Unified Protocol intervention will comprise 8 sessions of a 1 hour duration each. After the intervention, participants will answer the post-assessment protocol. Additional follow-up assessments will be conducted at one, three, six and twelve months after the intervention. Primary outcomes will be anxiety and depressive symptoms. Secondary outcomes include quality of life, emotion dysregulation, distress tolerance, and satisfaction with the programme. Data analyses will include between-group and within-group differences and visual analysis of patients' progress. Discussion: Results from this study will be disseminated in scientific journals. These findings may help to provide valuable information in the implementation of psychological interventions for patients suffering post COVID-19 conditions.